Balancing Risks and Benefits: Stakeholder Perspective on Managing Non-Native Tree Species in the European Alpine Space - Reneema Hazarika; Katharina Lapin; Anja Bindewald; Ana Sofia Vaz; Aleksander Marinšek; Nicola La Porta; Patricia Detry; Frédéric Berger; Darja Barič; Anica Simčič; Harald Vacik (Mitigation and Adaptation Strategies for Global Change, 2024)
For centuries, non-native tree (NNT) species have been planted throughout Europe for ecosystem services including timber and urban greenery. Public interest in NNTs has recently increased due to their potential role in climate change adaptation as alternatives to vulnerable native forest tree species. However, opinions regarding the benefits and risks of European NNTs differ. Understanding stakeholder perceptions is crucial for guiding adaptive forest management, especially in sensitive ecosystems like the European Alpine Space. To assess awareness and perception, a structured questionnaire was administered to 456 respondents from six countries in the European Alpine Space. Most respondents were aware of the origin of native and NNT species in their area. NNTs and invasive-NNTs were primarily found in urban regions, with a perceived increase in their occurrence over the past 25~years. With some exceptions, such as Pseudotsuga menziesii ( Mirb .) Franco, the most common NNTs were generally perceived as potentially invasive. The perception of the invasiveness of NNTs correlated with their perceived risks and benefits on ecosystem services. The respondents who were unconcerned about invasiveness believed NNTs had a positive impact on provisioning services like timber, while those concerned about invasiveness perceived their negative effects on regulating cultural ecosystem services such as native biodiversity and landscape aesthetics. Overall, most respondents were conservative, opposing the promotion of NNTs, even in biodiversity-poor areas. Most stakeholders also believe that NNT regulations should prioritize their sustainable use and management rather than focusing solely on an invasive-centric narrative.
Keywords: 330; Climate change adaptation; Ecosystem services; European Alpine Space; Invasiveness; Non-native trees; Perception